Analisis Yuridis Smart Contract di Indonesia: Antara Living Law dan Social Engineering - Setyo Pamungkas; Abigail Prasetyo; Selvi Novitasari; Sri Harini Dwiyatmi; Rasendria BP (Jurnal Hukum Lex Generalis, 2026)
The advancement of blockchain technology has given rise to the concept of smart contracts as an innovation in the execution of automated agreements based on computer code. This research aims to analyze the legal standing of smart contracts within the Indonesian legal system and examine the issues arising in global practice. The research method employed is normative legal research with statutory and conceptual approaches. The findings indicate that while smart contracts are not yet explicitly regulated under Indonesian positive law, they can be implicitly recognized through the electronic contract regime. In global practice, cases such as "The DAO Hack" demonstrate the potential for disputes resulting from code vulnerabilities. Therefore, adaptive regulation is required to ensure legal certainty, justice, and utility.